'Alarmist stories and defeatist views': Censorship and morale in India during the Second World War. (April 2019) - Sethi, Devika
This article identifies three loci of the British colonial state's anxiety about communication of news and views in India during the Second World War: its own officials (and their families); the press (both English language and vernacular); and the Indian public. It explores war-time dilemmas of the state with regard to censorship of both news and rumour, and it discusses the central paradox of censorship in colonial India during war-time.